2005
DOI: 10.1101/gr.4421405
|View full text |Cite
|
Sign up to set email alerts
|

Sequence features in regions of weak and strong linkage disequilibrium

Abstract: We use genotype data generated by the International HapMap Project to dissect the relationship between sequence features and the degree of linkage disequilibrium in the genome. We show that variation in linkage disequilibrium is broadly similar across populations and examine sequence landscape in regions of strong and weak disequilibrium. Linkage disequilibrium is generally low within ∼15 Mb of the telomeres of each chromosome and noticeably elevated in large, duplicated regions of the genome as well as within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 54 publications
8
93
2
1
Order By: Relevance
“…However, in the human genome, high LD in coding regions has been reported to be associated with sequence conservation in mouse sequences (Kato et al, 2006). Some repeats were also associated with regions of high LD (LINE repeats) or weak LD (SINE repeats, Alu sequences) (Smith et al, 2005). In this study, no relationship was found between LD and nucleotide diversity, an indicator of sequence conservation.…”
Section: Ld Patternscontrasting
confidence: 39%
See 1 more Smart Citation
“…However, in the human genome, high LD in coding regions has been reported to be associated with sequence conservation in mouse sequences (Kato et al, 2006). Some repeats were also associated with regions of high LD (LINE repeats) or weak LD (SINE repeats, Alu sequences) (Smith et al, 2005). In this study, no relationship was found between LD and nucleotide diversity, an indicator of sequence conservation.…”
Section: Ld Patternscontrasting
confidence: 39%
“…LD can also be highly variable between chromosomes and between different regions within chromosomes (Yan et al, 2009). Highly heterogeneous levels of LD were also described along the human genome, which could be partially correlated with sequence features (Smith et al, 2005).…”
Section: Ld Patternsmentioning
confidence: 98%
“…Although the majority of gene classes are equally divided between these two extreme quartiles of the genome, some classes of genes show a marked skew in their distribution 64,84,85 . Genes involved in immune responses and neurophysiological processes are more often located in regions of low LD, whereas genes involved in DNA and RNA metabolism, response to DNA damage and the cell cycle are preferentially located in regions of strong linkage disequilibrium.…”
Section: Insights Into Recombination and Natural Selectionmentioning
confidence: 99%
“…9 -12 The recently published HapMap dataset allowed for the first time the identification of functional categories of genes that are preferentially located within regions of weak LD (immune response and sensory perception) and strong LD (DNA and RNA metabolism and cell cycle). 13,14 In addition, several functional categories related to neurotransmission showed reduced LD. 13 These LD patterns result from the joint influence of drift and different modes of selection on multiple sites under a complex population history.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition, several functional categories related to neurotransmission showed reduced LD. 13 These LD patterns result from the joint influence of drift and different modes of selection on multiple sites under a complex population history. Nevertheless, the biased LD patterns gave rise to the hypothesis that it could be advantageous for certain types of genes to be located in regions of increased recombination.…”
Section: Introductionmentioning
confidence: 99%